PENGARUH KINERJA PENGURUS KOPERASI TERHADAP PARTISIPASI ANGGOTA KOPERASI BAYDURI PERMAI KECAMATAN MANDAU - Robbi, Anni Attika; Indrawati, Henny; Haryana, Gani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack: The cooperative is a business entity whose members are individuals or legal entity with the bases cooperative activities based on the principle of cooperation as well as peoples economic movement based on the principle of kinship. The purpose of cooperatives is to fight for the satisfaction of individual goals of its members. This research was conducted in the savings and loan cooperatives Bayduri Permai address at Jl. Rokan Mandau. The population in this study are all members of the cooperative Bayduri districts Mandau totaling 46 people . However, because the board is not used as a sample, the sample of the research in is the number of members , as many as 40 people. This research data in the form of a questionnaire distributed to all members of the cooperative. The data in this study normal distribution is by Taraf Sig . < Value Asymp.Sig . ( 0.05 < 0.918 and 0.832). The study hypothesis was that there is a significant influence on the participation of members of the board s performance is met where the value of the F test 38.852 > 0.05. So a significant difference between the performance variable board member participation . The coefficient of determination based on the test , there are significant performance variables by 50.6 % to variable participation. For Bayduri cooperatives in order to maintain performance management is variable due to poor performance or both will have an impact and influence on the participation of members.Keywords: Board Performance, Participation Of Members